PENGARUH PENDAPATAN PREMI DAN BEBAN KLAIM TERHADAP RETURN ON EQUTY PERUSAHAAN ASURANSI JIWA - Sari Bangun, Devi Permata; Priyanto, Aria Aji (Journal of Research and Publication Innovation, 2024)
This research aims to examine the influence of premium income and claim expenses on the return on equity in life insurance companies registered with the Financial Services Authority (OJK) from 2013 to 2022. The method employed is quantitative research. The data analysis technique involves Descriptive Statistical Analysis, Classical Assumption Test, Regression Model, Model Selection Method, Panel Data Regression Analysis, Hypothesis Testing, and the use of EViews software version 12. The research results indicate that: (1) simultaneously, premium income and claim expenses significantly affect the return on equity of life insurance companies, with an F-statistic value where the probability (0.000000 < 0.05), (2) individually, the premium income variable does not have a significant effect on the return on equity of life insurance companies, with a t-statistic value of 1.976049 and a probability of 0.0513 > 0.05. However, the claim expenses variable individually has a significant effect on the return on equity of life insurance companies, with a t-statistic value of -2.846803 and a probability of 0.0055 < 0.05.